2008
DOI: 10.1007/s10741-008-9105-y
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic dysfunction in exercise and its role for exercise capacity

Abstract: Diastolic dysfunction is frequent in elderly subjects and in patients with left ventricular hypertrophy, vascular disease and diabetes mellitus. Patients with diastolic dysfunction demonstrate a reduced exercise capacity and might suffer from congestive heart failure (CHF). Presence of symptoms of CHF in the setting of a normal systolic function is referred to as heart failure with normal ejection fraction (HFNEF) or, if evidence of an impaired diastolic function is observed, as diastolic heart failure (DHF). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 86 publications
(97 reference statements)
2
22
0
Order By: Relevance
“…In STG, we observed significant improvements of exercise capacity in terms of increased V O 2max and intermittent endurance capacity, respectively, and these findings mirror results of a meta-analysis of beneficial effects of structured exercise interventions on cardiorespiratory fitness in T2DM patients (8). LV diastolic dysfunction can contribute to reduced exercise capacity, for example, by promoting a disproportionate increase in LV filling pressures during exercise, impaired myocardial perfusion, and reduced ability to increase stroke volume (7,22,33). Therefore, improved LV diastolic function in STG is likely to have significantly added to the increased exercise capacity observed in this group.…”
Section: Discussionmentioning
confidence: 99%
“…In STG, we observed significant improvements of exercise capacity in terms of increased V O 2max and intermittent endurance capacity, respectively, and these findings mirror results of a meta-analysis of beneficial effects of structured exercise interventions on cardiorespiratory fitness in T2DM patients (8). LV diastolic dysfunction can contribute to reduced exercise capacity, for example, by promoting a disproportionate increase in LV filling pressures during exercise, impaired myocardial perfusion, and reduced ability to increase stroke volume (7,22,33). Therefore, improved LV diastolic function in STG is likely to have significantly added to the increased exercise capacity observed in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Several pathophysiological mechanisms have been suggested to be involved in the development of the clinical scenario that limits physical performance in HFNEF patients [4]. They include an inadequate increase of ventricular diastolic filling and cardiac output during exercise, consequently leading to pulmonary congestion [5]. Echocardiographic studies have shown that, in HFNEF patients undergoing exercise, an increasing proportion of late diastolic filling can lead to a drop of the early proportion of diastolic filling.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of diastolic dysfunction (DD) is common in elderly subjects and in patients with left ventricular hypertrophy, arterial hypertension, valvular disease, coronary artery disease, and/or diabetes mellitus. For the diagnosis of DD, evidence of slow left ventricular relaxation, abnormal left ventricular filling, reduced diastolic distensibility, or increased left ventricular stiffness is required . Even in an asymptomatic stage, patients with DD are characterized by reduced exercise capacity and are at risk for the development of heart failure (HF) .…”
Section: Introductionmentioning
confidence: 99%